Quality Of Life Of Thalassemia Major Patients - Fazalullah Khan, Fazalullah Khan; Isra Ali Nawaz, Isra Ali Nawaz; Aysha Asif, Aysha Asif; Abdul Rehman, Abdul Rehman (Students' Supplement of Journal of Rawalpindi Medical College, 2019)
Background: Thalassemia major is a chronic disease that presents as a range of serious clinical and psychological challenges. The effect of thalassemia on physical health can lead to deformity, growth retardation and delayed puberty. We conducted this study to assess quality of life of thalassemia major patients registered in thalassemia treatment centers of Rawalpindi. Methods: This descriptive cross-sectional study was done in TTC (Thalassemia Treatment Center) of HFH (Holy family hospital) and Thalassemia House in Rawalpindi from January 2018 to March 2018 after ethical approval from Institutional Research Forum of Rawalpindi Medical University. A total of 120 thalassemic patients ranging from 5 to 28 years of age brought for blood transfusion were included. Patients having impaired cognitive functions and those having multiple comorbidities were excluded. A modified version of WHO QOL BREF questionnaire was developed to assess the physical, psychological, environmental and social aspects of Quality of Life. Data was entered on SPSS v 22 and descriptive statistics were applied. Results: Out of 120 patients surveyed, majority were females (55.83 %) with a mean age of 10.22± 4.5 years. Forty four percent of the patients were males with mean age of 11.42± 5.19 years. Quality of life of these patients was found to be 68.8%. In females it was 69.34 % and in males it was 68.15%. Quality of life was significantly associated with psychological (p<0.05), social (p=0.009) and physical (p<0.05) factors. Poorer quality of life was found against environmental (financial resources, transport, healthcare) aspects (63.13%). Adverse impact of thalassemia was also found on physical (67.88%) and psychological (68.82%) quality of life of patients. Social Quality of life was found to be (92.3%). Conclusion: Poor psychological support along with other environmental and physical aspects lead to lower Quality of life of β thalassemia major patients. Proper management along with psychological support is essential for these patients. Key words: thalassemia, quality of life